The influence of nutrient medium on the reproduction of bacteriophages active against clinically significant microorganisms - Poniatovska , Valeriia; Poniatovskyi, Vadym; Shyrobokov, Volodymyr (The Ukrainian Scientific Medical Youth Journal, 2025)
іmproving bacteriophage cultivation methods, optimizing nutrient media composition, and implementing modern production technologies will significantly increase the yield and quality of phage preparations. Enhancing production efficiency is a crucial step toward expanding the potential of modern phage therapy, raising the ability to combat antibiotic-resistant microorganisms, and stimulating the development of innovative biotechnological solutions. One of the key factors in improving the efficiency of phage production is the selection of optimal cultivation parameters. Changes in the chemical composition of the medium can either slow down or accelerate the growth rate of the bacterial culture, thereby indirectly affecting phage replication. To determine the impact of nutrient media type on bacteriophage reproduction, five different bacteriological media and nine bacteriophages active against nine species of clinically significant microorganisms were used. The effect of media composition was assessed based on the number and size of plaque formations. Optimal replication of all nine bacteriophages was observed on Nutrient Agar No 1, which contained peptic digest of animal tissue, meat extract, and yeast extract. Additionally, good phage reproduction was noted on Mueller-Hinton Agar and Nutrient Medium. The least suitable medium for phage cultivation was Tryptic Soy Agar, where bacteriophage replication was the lowest. Improving cultivation methods and optimizing the composition of nutrient media for bacteriophage reproduction are crucial steps toward enhancing the efficiency of their production and application in phage therapy.